CBCT-3D radiographic analysis of an infected radicular cyst of the upper jaw: a case report - Prawira, Ade; Yunus, Barunawaty; Rahman, Fadhlil Ulum Abdul; Anam, Mukhtar Nur (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2024)
Objectives: The purpose of this case report is to find out the function of CBCT that can analyze in detail a radicular cyst case where CBCT has the ability to determine the density of a lesion. An overview of the density pattern of a radicular cyst can help determine the lesion and its margins. Case Report: : A 40-year-old patient complained of swelling in the palate that had been felt for about a year with a history of trauma due to an accident fifteen years ago. The patient underwent CBCT examination with the results of a hypodense area compared to the surrounding bone in the maxillary anterior area involving teeth 11,21,22 to 23 accompanied by a discontinuity of the cortical plate of the palatal bone and extending to involve the base of the nasal cavity. Part of the lesion is clearly demarcated, while the other side is diffuse. The suspected radiodiagnosis of the case was a moderately aggressive radicular cyst with a differential diagnosis of an odontogenic tumor. Conclusion: The final diagnosis of this case was a radicular cyst with chronic granulomatous inflammation, based on a combination of radiographic findings, clinical findings, and histopathological examination.